Synthesis of Graphene-Like Carbon from Coconut Shell and Electrical Conductivity Properties - Rohmat, Nur; Affi, Jon; Gunawarman; Handayani, Murni; Yetri, Yuli (Program Studi Teknik Mesin Universitas Pamulang, 2026)
Demand for batteries continues to increase in line with the growth of electric vehicles, while the availability of lithium in nature is limited. One alternative is the use of renewable natural materials, such as coconut shells, to produce functional carbon materials. This study aims to synthesize graphene-like carbon (GLC) from coconut shells using pyrolysis and sonication methods. The process was carried out through drying at 150–200 °C and pyrolysis at 700 °C. XRD characterization showed main peaks at 2θ ≈ 23.11° and 43.75° (150 °C/700 °C), and 23.15° and 43.38° (200 °C/700 °C), with an interlayer spacing of 0.35 nm and a shift in the C (002) peak from pure graphite, indicating the formation of nanosized graphene layers. FTIR analysis confirmed the presence of O–H, aromatic C=C, C=O, and C–O groups, indicating a hexagonal carbon framework with oxygen functionality on the surface. The Raman spectrum showed ID/IG ratios of 0.84 and 0.83, indicating structural disorder while still consistent with graphene-like characteristics. Conductivity tests showed relatively stable electrical conductivity with gradual electron energy loss at small current increases, allowing better control of electron mobility.